Comparison between Fractionated Dose versus Bolus Dose of Intrathecal Hyperbaric Bupivacaine Injection in Spinal Anesthesia for Patients Undergoing Elective Caesarean Section - Ullah, Muhammad Mizan; Rahman, Md Afzalur; Islam, Monirul; Amin, Wazed; Begum, Sharmin Ara; Alam, ABM Muksudul; Islam, Shahidul (Journal of Shaheed Suhrawardy Medical College, 2023)
Background: Spinal anesthesia (SA) with bolus dose has rapid onset but may causes hypotension. When we inject local anesthetic in fractions with a time gap, it provides more hemodynamic stability an. We aimed to compare fractionated dose with bolus dose in SA for hemodynamic stability in patients undergoing elective lower segment caesarean section (LSCS). Objectives: To find out whether the fractionated dose of spinal local anesthetics could reduce the incidence of hemodynamic changes in comparison to bolus dose of spinal local anesthetics. Methods: After clearance from the Institutional Ethics Committee, the study was carried out in 80 patients undergoing elective LSCS. Patients were divided into two groups. Group B patients received single bolus SA with injection bupivacaine heavy (0.5%) and Group F patients fractionated dose with 2/3rd of the total dose of injection bupivacaine heavy (0.5%) given initially followed by 1/3rd dose after 90 s. The intraoperative hemodynamics were recorded and analyzed with chi- square test Student’s t-test. Result: Intraoperative mean blood pressure of group –F were higher than those of Group-B patient and showed statistically significant difference. Mean heart rate of group –F were higher than those of Group-B patient and showed statistically significant difference. Conclusion: Fractionated dose of SA provides greater hemodynamic stability compared to bolus dose. J Shaheed Suhrawardy Med Coll 2021; 13(2): 150-157